2011
DOI: 10.1163/000579511x573917
|View full text |Cite
|
Sign up to set email alerts
|

Male phenotype predicts extra-pair paternity in pied flycatchers

Abstract: Extra-pair paternity has the potential to increase male reproductive success and in turn the potential for sexual selection to act on male traits predicting extra pair mate success. There is large variation among European populations of pied flycatchers (Ficedula hypoleuca) in the extent to which male traits predict success in extra pair mating behaviour. In an Iberian population with a relatively high proportion of extra-pair young multiple male traits were involved in extra pair paternity success. Cuckolder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 108 publications
(139 reference statements)
7
50
1
Order By: Relevance
“…Phenotypic traits that affect mate guarding ability or mate fidelity might also modify the relationship between breeding synchrony and rates of EPP (Canal et al ), but we found no evidence for this hypothesis with respect to either male age or body size. However, older white males lost more paternity, potentially reflecting senescent declines in mate‐guarding efficiency, sexual displays or sperm quality (Møller et al , Preston et al , Noguera et al ).…”
Section: Discussioncontrasting
confidence: 83%
“…Phenotypic traits that affect mate guarding ability or mate fidelity might also modify the relationship between breeding synchrony and rates of EPP (Canal et al ), but we found no evidence for this hypothesis with respect to either male age or body size. However, older white males lost more paternity, potentially reflecting senescent declines in mate‐guarding efficiency, sexual displays or sperm quality (Møller et al , Preston et al , Noguera et al ).…”
Section: Discussioncontrasting
confidence: 83%
“…A very interesting outcome of the inclusion of bachelor birds in the analysis is the fact that they seem to be able to achieve some paternity. Some studies report that the identity of a few extra‐pair fathers remained unknown, even when a high proportion of the breeding birds are identified (Canal et al ). These missing individuals could either be birds breeding outside of the study area or even floaters.…”
Section: Discussionmentioning
confidence: 99%
“…EPP has been shown to be affected by many factors, including secondary sex features (Møller et al , Lehtonen et al , Canal et al ), body size (Canal et al ), age (Moreno et al , Canal et al ), polygyny (Lubjuhn et al ), and timing of breeding (Canal et al , b). However, to date, the number of studies that have investigated how male arrival date associates with paternity (gain or loss) is small (Table ).…”
Section: Review Of Studies That Correlated Arrival Dates With Paternimentioning
confidence: 99%
“…In addition, as in the congeneric collared flycatcher ( Ficedula albicollis ; Gustafsson et al ., ; Qvarnström et al ., ; de Heij et al ., ), there is positive directional sexual selection in at least some Iberian populations of pied flycatchers on forehead patch size in males. Males with large forehead patches mate more quickly (Potti & Montalvo, ) and sire more extra‐pair offspring than males with smaller patches (Canal et al ., ). Although the magnitude of the cross‐sex genetic correlation in trait expression is unknown (all males express the trait, hence there is no variance in male trait expression), once expressed in females there is a strong positive genetic correlation between the sexes in trait size (Potti & Canal, ).…”
Section: Introductionmentioning
confidence: 97%